SIFAT-SIFAT DASAR INTEGRAL HENSTOCK - Sinay, Lexy J. (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2012)
This paper was a review about theory of Henstock integral. Riemann gave a definition of integral based on the sum of the partitions in Integration area (interval [a, b]). Thosepartitions is a ï¤ -positive constant. Independently, Henstock and Kurzweil replaces ï¤- positive constant on construction Riemann integral into a positive function, ie ï¤(x)>0 forevery xïƒŽ[a, b]. This function is a partition in interval [a, b]. From this partitions, we can defined a new integral called Henstock integral. Henstock integral is referred to as acomplete Riemann integral, because the basic properties of the Henstock integral is more constructive than Riemann Integral.